Duplication of Horizontally Acquired GH5_2 Enzymes Played a Central Role in the Evolution of Longhorned Beetles. (28th June 2022) - Shin, Na Ra; Doucet, Daniel; Pauchet, Yannick
Abstract: The rise of functional diversity through gene duplication contributed to the adaption of organisms to various environments. Here we investigate the evolution of putative cellulases of the subfamily 2 of glycoside hydrolase family 5 (GH5_2) in the Cerambycidae (longhorned beetles), a megadiverse assemblage of mostly xylophagous beetles. Cerambycidae originally acquired GH5_2 from a bacterial donor through horizontal gene transfer (HGT), and extant species harbor multiple copies that arose from gene duplication. We ask how these digestive enzymes contributed to the ability of these beetles to feed on wood. We analyzed 113 GH5_2, including the functional characterization of 52 of them, derived from 25 species covering most subfamilies of Cerambycidae. Ancestral gene duplications led to five well-defined groups with distinct substrate specificity, allowing these beetles to break down, in addition to cellulose, polysaccharides that are abundant in plant cell walls (PCWs), namely, xyloglucan, xylan, and mannans. Resurrecting the ancestral enzyme originally acquired by HGT, we show it was a cellulase that was able to break down glucomannan and xylan. Finally, recent gene duplications further expanded the catalytic repertoire of cerambycid GH5_2, giving rise to enzymes that favor transglycosylation over hydrolysis. We suggest that HGT and gene duplication, which shaped the evolution of GH5_2, played a central role in the ability of cerambycid beetles to use a PCW-rich diet and may have contributed to their successful radiation.